Peran Environmental, Social, and Governance (ESG) terhadap Price to Book Value (PBV) Saham PT Energi Mega Persada pada Periode 2022–2024 - Agung Budi Darmoyo; Vera Salma Meilania; Ovalia Rukmana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore the effect of Environmental, Social, and Governance (ESG) performance on the Price-to-Book Value Ratio (PBV) of PT Energi Mega Persada Tbk (EMP) during the period of 2022–2024, which was marked by global energy volatility and increased sustainability disclosure requirements, and to examine whether increased ESG disclosure in the Sustainability Annual Report can result in higher market valuations, especially in the energy sector, which faces scrutiny regarding corporate environmental, social, and governance transparency. Data collection was conducted through semi-structured interviews with two sources: the investor relations department of PT. Energi Mega Persada and representatives of the majority shareholders of ENRG, with the aim that investor relations have full access to public data and are considered valid to answer issues related to PBV, ESG, and corporate performance. Meanwhile, the majority shareholder's representative will influence the company's strategic direction and the majority investor's expectations regarding ESG, PBV, and company performance in a valid manner, and will also explain the majority shareholder's perspective to understand ESG issues, financial performance, and company strategy in an integrated manner. The analysis in this study uses a qualitative approach, supported by content analysis in NVivo, to explore how Environmental, Social, and Governance (ESG) disclosure relates to Book Value Price (PBV). The results show that ESG disclosure, overall, has a positive but variable effect on PBV. The environmental dimension contributes through emission-reduction initiatives and improved waste management, while the social dimension demonstrates consistency with increased CSR investment. Improvements in governance, such as establishing an ESG Committee, strengthen the company's credibility. PBV remained relatively stable throughout the observed period, reflecting stable investor confidence.